Expectations for competencies of top managers: changes and good practice - Markauskienė, Gintarė (Buhalterinės apskaitos teorija ir praktika, 2020)
As the economic situation develops, the competencies of top managers are subject to extremely high requirements. This starts with functional and formal leadership as well as clearly defined status and job functions. It ends with the image of a modern leader who possesses a myriad of competencies and character traits, the criteria of which change constantly. It is observed that the importance of competencies, cooperation between top managers, personal development and leadership are most often studied. There are no questions raised in the research that would analyse the change of competencies of top managers over time and expectations for competencies in a constantly changing environment. The aim of this article is to examine expectations of top managers’ competencies in context of good practices. To achieve this goal an analysis of the scientific literature was performed, systematisation and generalisation methods were used, good practice was observed and a survey was conducted. The results of the analysis of the scientific literature revealed which competence groups are most valued in today’s business environment, as well as what opportunities opened up and what challenges the quarantine regime posed for today’s leaders. The study identified key competencies, such as high ethical and moral standards and openness to new ideas and perspectives. The motivation behind the scientific problem formulated in this article was the lack of research and information, especially in view of the quarantine period, which significantly impacted the normal rhythm of work and life.